PrEP rollout in Africa: status and opportunity - Irungu, Elizabeth M.; Baeten, Jared M. (Nature medicine, 2020)
Following recommendations by the World Health Organization in 2015, and key clinical trials, countries in sub-Saharan Africa, the region with the highest burden of human immunodeficiency virus (HIV), developed policies that incorporate pre-exposure prophylaxis (PrEP) into national HIV-prevention strategies. By the end of 2019, more than one third of people receiving PrEP globally were in Africa. Crucial understandings gained from early rollout among at-risk populations, such as HIV-serodiscordant couples, adolescent girls and young women, female sex workers, and men who have sex with men, include the importance of strategies for maintaining persistent adherence to PrEP and novel approaches to making PrEP services accessible, simplified and efficient. This Perspective will discuss the current status of these programs and how to further widen their implementation. PrEP is being incorporated into national HIV-prevention strategies in African countries, with key at-risk populations being prioritized. Expansion of these programs will require better access to and communication about these therapies.